Departures: An Introduction to Critical Refugee Studies by the Critical Refugee Studies Collective (A Book Review) - Traina, Giacomo (Review of International American Studies, 2022)
Departures is the introductory volume to the interdisciplinary field of Critical Refugee Studies, written by the Critical Refugee Studies Collective and published by the University of California Press. The book works on many levels and can be read in as many ways. Partly a guide, partly a manifesto, the book dutifully performs its pre-set task of introducing the general reader to the field of Critical Refugee Studies, all the while engaging with larger issues and challenges. Its manifold nature is made explicit by the title itself, intended both as an allusion to the action of leaving and to that of deviating from a regular path. Highly readable and sharp-edged, tailor-made for an audience that includes (and transcends) colleges and universities, this text will likely find its way into many class syllabi and reading lists. Located at the crossroads of theory and resistance, advocacy and academia, Departures oozes rage, energy, and optimism, and is unapologetically political. The field of Critical Refugee Studies, the authors state in the “Introduction,” is “a way to seize control of image and narrative, by and for refugees, centered in refugee epistemologies and experiences." As a community-engaged critical field, it postulates the necessity of moving past pre-existing humanitarian narratives and frameworks, exposing the underlying threads that tie militarism and migration, power and memory, empire and race. Channeling Somali British and Palestinian poetry, Syrian visual art, and Vietnamese American independent cinematography, the seven contributors call for new methodologies and approaches, as well as for new stories that go beyond the simple “formula of … escape, despair, and rescue” embedded in mainstream refugee narratives. The book's aim is to break that mold, underscoring the “invisible relations of power that broker how we see and consume the refugee subject”; that is to say, to radically twist the ways in which the latter is defined by the law, by the arts, and by the collective conscious. Bold and provocative, Departures will not fail to spark conversations in the coming years.